2021
DOI: 10.1097/mjt.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Direct Oral Anticoagulants Versus Vitamin K Antagonists in the Treatment of Left Ventricular Thrombus: A Systematic Review and Meta-analysis

Abstract: Background: Left ventricular thrombus (LVT) may develop in systolic heart failure or after acute myocardial infarction. The current recommendations support the use of vitamin K antagonists (VKAs) for the treatment of LVT. Limited data exist regarding the use of direct oral anticoagulants (DOACs) in patients with LVT. This meta-analysis aims to investigate the efficacy and safety of DOACs versus VKAs for LVT. Methods: We performed a comprehensive literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Several meta-analyses reported results similar to ours. Burmeister et al (2021 concluded) that patients with NOACs showed a higher rate of thrombus regression (risk ratio = 1.18, 95% confidence interval 1.04–1.35, p = 0.01) while there was no significant difference between the NOACs and VKA groups in stroke, thromboembolism, or any bleeding event [ 24 ]. Two reviews, Saleiro et al [ 18 ] and Camilli et al [ 39 ], comparing NOACs and VKAs in patients with left VT have been published; while the former paper suggested that NOACs were as effective as VKAs for VT with a similar risk of thromboembolism/stroke and bleeding, the latter paper concluded that NOACs were comparable to VKA in terms of thrombus resolution, providing lower bleeding rates and an increase in thromboembolism events in the NOACs group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses reported results similar to ours. Burmeister et al (2021 concluded) that patients with NOACs showed a higher rate of thrombus regression (risk ratio = 1.18, 95% confidence interval 1.04–1.35, p = 0.01) while there was no significant difference between the NOACs and VKA groups in stroke, thromboembolism, or any bleeding event [ 24 ]. Two reviews, Saleiro et al [ 18 ] and Camilli et al [ 39 ], comparing NOACs and VKAs in patients with left VT have been published; while the former paper suggested that NOACs were as effective as VKAs for VT with a similar risk of thromboembolism/stroke and bleeding, the latter paper concluded that NOACs were comparable to VKA in terms of thrombus resolution, providing lower bleeding rates and an increase in thromboembolism events in the NOACs group.…”
Section: Discussionmentioning
confidence: 99%
“…2017 European guidelines also recommended that STEMI patients with left VT should maintain anticoagulation therapy for up to 6 months under the guidance of repeated imaging ( Class II a, level C evidence ) [ 11 ]. Up to date, quite a few studies reported that NOACs had comparable safety and efficacy outcomes in the treatment of VT [ 12 24 ]. Michael et al (2021) conducted a meta-analysis to compare NOACs to VKAs for the treatment of left ventricular thrombus, including a total of 18 studies with 2666 patients, and their result showed that NOACs had less 37% risk of stroke than VKAs, while no significances were observed in thrombus resolution, systemic embolism, bleeding, or all-cause death events.…”
Section: Introductionmentioning
confidence: 99%
“…No stroke or embolism events were observed, and only one patient experienced nonfatal bleeding. Numerous studies claimed that NOACs were comparable with or even outweighed VKAs [28,[33][34][35][36][37]39,40,[45][46][47], and obviously the most popular or dominant usage of NOACs was rivaroxaban in all studies. It was known that NOACs could be divided into two types targeting various action mechanismanti-Xa inhibitor (rivaroxaban, apixaban and edoxaban or anti-IIa inhibitors (dabigatran).…”
Section: Discussionmentioning
confidence: 99%
“…LVTs have been found to persist even in the setting of percutaneous coronary intervention in the post-MI setting [15]. Current guidelines recommend the use of DOACs, as evidence is largely supportive of efficacy and resolution of thrombosis [16][17][18][19]. Vitamin K antagonists have traditionally been used, but due to the difficulties of monitoring the INR, it can be difficult in the setting of other drug and food interactions [20].…”
Section: Oral Anticoagulation Therapymentioning
confidence: 99%